The Effect of the Cooperative Model With the Assistance of LKS on Class III Students' Learning at SDN Bumianyar II - Astuti, Yeni Puji (Widyagogik, 2023)
Learning in general is a process of interaction between educators, students and their environment. Learning is a series of complex activities, in essence not only conveying subject matter but also requires the teacher to use all the basic skills in teaching. This study aims to examine: 1) significant differences in learning outcomes using the cooperative model with the help of LKS and conventional learning; 2) student activities in learning by using cooperative models with the help of worksheets. This type of research is experimental research. This experimental research design uses a control group pre-test-post-test design pattern. Data collection techniques using observation, interviews, documentation and tests. The data analysis technique uses the t-test statistical test formula and the percentage of student activity. The results of this study showed that there was a significant difference between learning outcomes using the Cooperative Model with LKS Assistance and conventional learning, as well as the percentage value of student activity while participating in learning using the Cooperative Model with classical LKS Assistance of 78.43% included in the active criteria. The conclusion of this study is that there is a significant difference between learning outcomes using the Cooperative Model with the help of LKS and conventional learning in Class III students of SDN Bumianyar II Academic Year 2020/2021 and the learning activities of class III students of SDN Bumianyar II Academic Year 2020/2021 while participating in learning using The Cooperative Model with the Help of LKS is included in the active category.